2022
DOI: 10.1038/s41598-022-08419-2
|View full text |Cite
|
Sign up to set email alerts
|

Insights into countries’ exposure and vulnerability to food trade shocks from network-based simulations

Abstract: In the context of a global food system, the dynamics associated to international food trade have become key determinants of food security. In this paper, we resort to a diffusion model to simulate how shocks to domestic food production propagate through the international food trade network and study the relationship between trade openness and vulnerability. The results of our simulations suggest that low-income and food insecure countries tend to be the more exposed to external shocks and, at the same time, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Trade globalization has shown an increase in food resilience and water security, whereas it also enhanced the likelihood of global crises due to growing dependence on major production hubs [ 74 , 83 , 84 ]. Overall, the topological quantification of Indian inland trade through a complex system’s lens could help to understand the trade network’s resilience and recovery by identifying the network’s important and vulnerable sections to external disruptions.…”
Section: Discussionmentioning
confidence: 99%
“…Trade globalization has shown an increase in food resilience and water security, whereas it also enhanced the likelihood of global crises due to growing dependence on major production hubs [ 74 , 83 , 84 ]. Overall, the topological quantification of Indian inland trade through a complex system’s lens could help to understand the trade network’s resilience and recovery by identifying the network’s important and vulnerable sections to external disruptions.…”
Section: Discussionmentioning
confidence: 99%
“…A breakdown shows that 7% of the land area h high suitability for SSM (value: 21-25) and 17% as high suitability (value: 17-20), p located in the South and coastal regions. Meanwhile, the North Central region 33% area with moderate suitability surface soil moisture (value: [13][14][15][16]). The core N areas have 23% and 20% of their area classified as marginal (value: 8-12) and low ity (value: 3-8), respectively (see Figure 3).…”
Section: Environmental Suitability Potential Assessment For Agriculturementioning
confidence: 99%
“…Based on the above, to find a solution to food supply challenges, countries rely on food imports as a food security strategy to support local food production [15]. However, this option is also dependent on economic purchasing power, and this measure may not be sustainable due to various factors such as population growth [16] compared to advocating for self-sufficiency [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, models of the relationships between population growth, food production, and trade dynamics have shown that over-dependence on food imports impairs global food security (Suweis et al, 2015). Low-income food-deficit regions, such as Africa, the Middle East, and Latin America, are most vulnerable to price shocks in food trade and least able to protect themselves against domestic food production shocks (Grassia et al, 2022). Worse still, the UN International Labor Organization said in its 2021 report that people in these countries live with much lower rates of social welfare protection.…”
Section: Livelihood Struggle Among the Rural Poormentioning
confidence: 99%